2023
DOI: 10.1021/acs.estlett.3c00293
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Prediction of Enzymatic Degradation of Plastics Using Encoded Protein Sequence and Effective Feature Representation

Abstract: Enzyme biocatalysis for plastic treatment and recycling is an emerging field of growing interest. However, it is challenging and time-consuming to identify plastic-degrading enzymes with desirable functionality, given the large number of putative enzyme sequences. There is a critical need to develop an effective approach to accurately predict the enzyme activity in degrading different types of plastics. In this study, we developed a machine-learning-based plastic enzymatic degradation (PED) framework to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Recently, machine learning was implemented to develop the plastic enzymatic degradation (PED) framework . This PED framework can predict the ability of an enzyme to degrade plastics by analyzing protein sequences to identify specific patterns.…”
Section: Genetic Tools To Engineer Degradation Activities Of Polymer-...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, machine learning was implemented to develop the plastic enzymatic degradation (PED) framework . This PED framework can predict the ability of an enzyme to degrade plastics by analyzing protein sequences to identify specific patterns.…”
Section: Genetic Tools To Engineer Degradation Activities Of Polymer-...mentioning
confidence: 99%
“…Recently, machine learning was implemented to develop the plastic enzymatic degradation (PED) framework. 117 This PED framework can predict the ability of an enzyme to degrade plastics by analyzing protein sequences to identify specific patterns. The framework outperformed many other sequence-based classification models and identified that hydrophobicity, heat capacity, frequency of occurrence of alanine in the sequence, and the enzyme’s molecular weight are the most important structural motifs for an enzyme to degrade plastics.…”
Section: Genetic Tools To Engineer Degradation Activities Of Polymer-...mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Similarly, MutCompute was applied to TfCut2 wild type cutinase to identify beneficial mutations and create an enhanced variant, which exhibited a 5.3-fold improved depolymerization of crystalline PET. [31]] Most recent examples include the adoption of machine learning-assisted prediction of the degrading activity of certain plastics [32] or the use of machine learning to guide the directed evolution of plastic degrading enzymes. [33] This paper has applied different approaches such as structure-based design, ancestral sequence reconstruction and machine learning to engineer a new variant of PsPETase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the improvement of known enzymes, new PLA-degrading enzymes, with desirable properties, can be discovered using novel bioinformatic computational prediction methods. As sequence similarity does not consistently correlate with the functional ability of enzymes to degrade plastics, a machine learning-based approach was recently developed for the prediction of such enzymes (Jiang et al 2023 ). The system integrated data of a wide range of plastic-degrading enzymes, including PLA depolymerases like CLE and PlaM4, and could successfully establish sequence-based protein classification models.…”
Section: Introductionmentioning
confidence: 99%